Economy Pandemic: A Crisis Management towards Post COVID-19. A Commentary Opinion - Mani Man Singh Rajbhandari (Journal of Interdisciplinary Sciences)
COVID-19 Corona Virus pandemic is not only destroying the lives of people but it is equally scattering the economic lives of people all around the world. The COVID 19 pandemic has led to a widespread economic shut down thus raising the issue of post effect of COVID-19 towards the global economy. It has become a global economic crisis and brought about an economic pandemic to humankind with unemployment, business closure, shut down or fast tract economic boosting plans. The purpose of this study is to shed theoretical perspectives towards crisis management to boost growth for organizational economy. Theories of economic and management were interconnected to analyse this study on scientific realities. However, an economic pandemic may not be hard to overcome if crisis management is applied strategically through business diversification but not by crisis avoidance and crisis ignorance. Crisis management is all about having a newer vision through business diversity by creating newer business lines and creating spaces for small and medium enterprises and cottage industries to operate. This further enhances employment and keeps the purchasing power equilibrium intact for stagnant demand and supply ratio. This crisis management can be maintained through diversity management and the best strategic option is the pruning diversity strategy. Crisis ignorance and crisis avoidance are situational but that crisis management is long term.